Like father, like son: the intergenerational cycle of adolescent fatherhood. - Sipsma, Heather; Biello, Katie Brooks; Cole-Lewis, Heather; Kershaw, Trace (American journal of public health, 2010)
Strong evidence exists to support an intergenerational cycle of adolescent fatherhood, yet such a cycle has not been studied. We examined whether paternal adolescent fatherhood (i.e., father of study participant was age 19 years or younger when his first child was born) and other factors derived from the ecological systems theory predicted participant adolescent fatherhood.
Keywords: Adolescent; Adolescent Behavior; Adolescent Psychology; Ecology; Father-Child Relations; Fathers; Female; Humans; Intergenerational Relations; Juvenile Delinquency; Male; Multivariate Analysis; Paternal Age; Pregnancy; Pregnancy in Adolescence; Proportional Hazards Models; Prospective Studies; Psychological Theory; Regression Analysis; Risk Factors; Systems Theory; United States